ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH PROGRAM UPSUS PAJALE DI KECAMATAN KUMPEH ULU - Edison; Widya Sari, Arni; Sri Nurchaini, Dewi (Universitas Jambi, 2019)
Kumpeh Ulu subdistrict is one of the centers of rice production in Muaro Jambi district that follows the Upsus Pajale program. This research aims to (1) determine the effect of land area, seeds, fertilizers, pesticides and labor on the production of Upsus program and Non Upsus rice field in Kumpeh Ulu subdistrict (2) knowing the effect of Upsus Pajale on increasing rice production in the Kumpeh Ulu subdistrict. The research location was chosen intentionally (purposive) in the village of Pudak and Teluk Raya village. The number of samples was calculated by Slovin method and obtained as many as 76 farmers of paddy rice consisting of 38 program Upsus farmers and 38 non Upsus farmers. Selecting the sample was used by simple random sampling method. The analysis in this research used Cobb-Douglas analysis and Chow test. The results showed that the Upsus and Non Upsus program that affected production factors included a land area of 0.18%, seeds of 0.42%, Urea fertilizer of 0.41%, SP36 fertilizer of 0.09%, pesticides of 0.28% and dummy variables of 0.02%. While labor production factors did not significantly affect the production of rice Upsus and Non Upsus program. The results of the comparison test of the Upsus program and Non Upsus production function models were not significantly different. While the results of the comparative test of the combined Upsus program and Non Upsus production function model without dummy with the combined Upsus program and Non Upsus (dummy) production function model were significantly diferrent from f count of 6,919 greater than f table. This meant that there was a Upsus Pajale program effect on the increase in rice production in the research area where Upsus program production was 3.986 kg/ha higher than the Non Upsus production was 2.829 kg/ha.